Evolution of approaches to intellectual property’s classification - Virchenko V. (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Article is devoted to analysis of the theoretical approaches to intellectual property classification. History of development of theoretical approaches to intellectual property classification is investigated. Advantages and disadvantages of different approaches to intellectual property classification are considered. The contents and peculiarities of incorporate intellectual property are analyzed.